Evaluasi Implementasi Program Pelayanan Kesehatan Peduli Remaja (PKPR) di Puskesmas Andalas Kota Padang Tahun 2025 - Aziza, Lativa; Dian Paramitha Asyari; Meta Dwi Andriani (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Adolescence is a phase that is vulnerable to various physical, mental, and social health problems. This study aims to evaluate the implementation of the Adolescent Care Health Service Program (PKPR) at the Andalas Public Health Center in Padang City based on the aspects of input, process, and output. The research used a qualitative method with a descriptive approach through interviews, observations, and document reviews. The results show that in terms of input, policies and guidelines are available, but facilities, infrastructure, and health workers remain limited. In the process aspect, activities have been planned and organized; however, health promotion in schools is not yet optimal and no specific room for PKPR services is available. Regarding the output, adolescent health services are running but have not yet met national targets. Overall, the implementation of PKPR at the Andalas Health Center is not yet optimal, requiring improved facilities, coordination, and continuous evaluation.